Small volume platelet concentrates for neonatal use are more susceptible to shear-induced storage lesion - Dean Pym; Amanda J. Davies; Jessica O. Williams; Christine Saunders; Chloë E. George; Philip E. James (Platelets)
The impact of the biophysical environment on the platelet storage lesion (PSL) has mainly focused on reduced temperature storage, overlooking the significance of storage-induced shear stress. Shear stress in platelet storage refers to the frictional force acting parallel to the bag surface and exists solely through the implementation of agitation. This study investigates whether minimizing exposure to agitation-induced shear stress can alleviate the unexplained loss of function in stored platelet concentrates for neonatal transfusion (neonatal PCs). Using particle tracking analysis, fluid motion was measured in neonatal and adult platelet storage bags under agitation frequencies ranging from 20–60 rpm. Platelets stored at 20-60 rpm agitation over 8 days were examined by biochemical analysis, aggregation, and expression of activation markers. Results indicate that neonatal PCs experience significantly higher storage-induced shear stress compared to adult doses, leading to reduced functionality and increased activation from day 2 of storage. Adjusting the neonatal PC agitation frequency to 20 rpm improved functionality in early storage, while 40 rpm maintains this improvement throughout storage with reduced activation, compared to 60 rpm storage. This study confirms that small volume PC storage for neonatal use contributes to the PSL through the induction of shear stress, suggesting further evaluation of the recommended agitation frequency for neonatal PCs or postponement of the production of neonatal PCs until requested for neonatal transfusion.